2023
DOI: 10.3390/s23156880
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Layer Feature Fusion Method for Few-Shot Image Classification

Abstract: In image classification, few-shot learning deals with recognizing visual categories from a few tagged examples. The degree of expressiveness of the encoded features in this scenario is a crucial question that needs to be addressed in the models being trained. Recent approaches have achieved encouraging results in improving few-shot models in deep learning, but designing a competitive and simple architecture is challenging, especially considering its requirement in many practical applications. This work propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…According to the process setup of the few-shot image classification task [ 33 ], the given image dataset is randomly partitioned into three subsets, i.e., the base class dataset , the validation dataset , and the novel class dataset . These three subsets, which have different class labels, are used for the training of the model, the validation of the model, and the few-shot testing, respectively.…”
Section: Main Approachmentioning
confidence: 99%
“…According to the process setup of the few-shot image classification task [ 33 ], the given image dataset is randomly partitioned into three subsets, i.e., the base class dataset , the validation dataset , and the novel class dataset . These three subsets, which have different class labels, are used for the training of the model, the validation of the model, and the few-shot testing, respectively.…”
Section: Main Approachmentioning
confidence: 99%
“…No research has been found where disease classification is conducted on a self-collected dataset comprising more than 70 classes. However, the research by Cui et al [156] and Gomes et al [157] employs very interesting techniques that deserve mention. The same classification approach was utilized in a joint project with the Temiryazev Academy as part of the World-class Scientific Center "Agrotechnologies of the Future" [158].…”
Section: Mlit Activities Related To Artificial Intelligence In Agricu...mentioning
confidence: 99%